Characterization of the Cartilage DNA Methylome in Knee and Hip Osteoarthritis. Issue 9 (September 2014) - Rushton, Michael D.; Reynard, Louise N.; Barter, Matt J.; Refaie, Ramsay; Rankin, Kenneth S.; Young, David A.; Loughlin, John
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to characterize the genome‐wide DNA methylation profile of chondrocytes from knee and hip cartilage obtained from patients with osteoarthritis (OA) and hip cartilage obtained from patients with femoral neck fracture, providing the first comparison of DNA methylation between OA and non‐OA hip cartilage, and between OA hip and OA knee cartilage. Methods The study was performed using the Illumina Infinium HumanMethylation450 BeadChip array, which allows the annotation of ∼480, 000 CpG sites. Genome‐wide methylation was assessed in chondrocyte DNA extracted from 23 hip OA patients, 73 knee OA patients, and 21 healthy hip control patients with femoral neck fracture. Results Analysis revealed that chondrocytes from the hip cartilage of OA patients and healthy controls have unique methylation profiles, with 5, 322 differentially methylated loci (DMLs) identified between the 2 groups. In addition, a comparison between hip and knee OA chondrocytes revealed 5, 547 DMLs between the 2 groups, including DMLs in several genes known to be involved in the pathogenesis of OA. Hip OA samples were found to cluster into 2 groups. A total of 15, 239 DMLs were identified between the 2 clusters, with an enrichment of genes involved in inflammation and immunity. Similarly, we confirmed a previous report of knee OA samples that also clustered into 2 groups. Conclusion We demonstrated that global DNA methylation using a high‐density array can be a powerful tool in the characterization of OA at the molecular level. Identification of pathways enriched in DMLs between OA and OA‐free cartilage highlight potential etiologic mechanisms that are involved in the initiation and/or progression of the disease and that could be therapeutically targeted.